Analisis Perhitungan Harga Pokok dan Harga Jual pada UD. Barokah Kesamben - Rizky Wahyu Ramadhan; Lis Setyowati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The research aims to obtain results from the calculation of the cost of production and product selling prices from UD. Baroque. The data studied were from the results of company transactions and interviews with company owners.The method applied by the reviewers is descriptive qualitative using interviews and documentation.Based on this study, it states that the calculation of the cost price and selling price of UD. Barokah does not calculate the entire factory overhead expense, but the prices given by large companies have met the profit expected by UD. Barokah at a price of Rp. 700-800/Kg.